Search for a Higgs boson produced in association with a Z boson in p(p)over-bar collisions - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Elsevier B.V., 2007)
We describe a search for the Standard Model Higgs boson with a mass of 105 GeV/c(2) to 145 GeV/c(2) in data corresponding to an integrated luminosity of approximately 450 pb(-1) collected with the D phi detector at the Fermilab Tevatron p (p) over bar collider at a center-of-mass energy of 1.96 TeV. The Higgs boson is required to be produced in association with a Z boson, and the Z boson is required to decay to either electrons or muons with the Higgs boson decaying to a b (b) over bar pair. The data are well described by the expected background, leading to 95% confidence level cross section upper limits sigma (p (p) over bar -> ZH) x B(H -> b (b) over bar) in the range of 3.1 pb to 4.4 pb. (C) 2007 Elsevier B.V. All rights reserved.